Are relational capital and marketing important? The case of the wood sector of Galicia (Spain) and Portugal - Fernandez Jardón, Carlos-Maria; da Silva, Amândio F. C. (Business: Theory and Practice, 2023)
This paper examines the importance of marketing and relational capital in value addition. We studied the effect that relational capital has in the timber and related industries of Galicia (Spain) and Portugal for 2002–2018. The industry is characterized by a large number of SMEs, many of them operating in the subsistence and unorganized sectors. Direct marketing and personal contacts with clients are forms of enhancing the relational capital and to add value. The wood sector was divided into three major groups, namely: extraction, conversion and finished products, and using a panel data model, the value addition created by relational capital and the effect that direct marketing can have on the business were measured. While relational capital helps in creating value, its effect is not the same in every sector, implying that much has to be done by managers and CEOs to improve company relationships with stakeholders to develop business alliances.